Hygrothermal transfers through a bio-based multilayered wall: Modeling study of different wall configurations subjected to various climates and indoor cyclic loads. (January 2023) - Reuge, Nicolas; Collet, Florence; Pretot, Sylvie; Moisette, Sophie; Bart, Marjorie; Style, Oliver; Shea, Andy; Lanos, Christophe
The hygrothermal behavior of a bio-based multilayered wall has been studied by numerical simulations. The key point of these research investigations was to properly describe the hygrothermal transfers occurring inside the studied wall solution. In previous work, the case of the wall subjected to a given real climate (Wroughton HIVE demonstrator, UK, Feb 2018) has been investigated. The present work, focused on the moisture regulation capacity of the wall, considers an improved kinetics model of sorption, different layer configurations, one additional climate (Bordeaux, FR, Apr 2008) and the effect of indoor cyclic loads. Compared to the classical approach, the local kinetics approach results in prediction of stronger and steeper hygric dynamics with larger relative humidity variations at small time scales. The study of the different wall configurations allows to determine the best one in terms of moisture damping: the vapor control membrane is advantageously removed provided the OSB3 12 mm layer is replaced by an OSB4 18 mm layer. Moreover, the simulations show that the Moisture Buffer Value characteristic of each material layer is not a sufficient criterion to evaluate hygric performance of the wall; strong hygric interactions occur with the layer's permeability independently of its sorption capacity. Finally, water content hysteresis phenomena are studied and it appears that under usual operating conditions, they can be ignored by adjusting the layers' permeabilities for adequate fits on the Moisture Buffer Value tests.